Variability in protein patterns for virulence among the Rhizoctonia solani Isolates causing banded leaf and sheath blight in maize - P. NARAYAN REDDY and R. RANGA REDDY, M. MADHAVI*, K. MANOHAR (Indian Phytopathology, 2016)
Gel electrophoresis of fungal proteins has been used as an adjunct to morphological criteria in taxonomy for delineation of genera, species, and subspecies of various fungi. Variability in electrophoretic protein pattern among the population of Banded Leaf and Sheath Blight fungus Rhizoctonia solani in Andhra Pradesh was assessed from twenty seven isolates collected from different maize varieties and one from rice grown in various regions of Andhra Pradesh for easy breeding task. The R. solani isolates regardless of the locality from where they have been collected showed variation in the number of bands and their position. SDS- PAGE of total soluble proteins in fungal mats of the isolates of R. solani resolved into 125 bands of different intensities and densities. Qualitative and quantitative differences were noted among protein subunits of the isolates collected from different locations in Andhra Pradesh. Band number 3 with relative mobility 0.09 is common in most of the isolates followed by band 15 with 0.25 relative mobility. However band 36 with relative mobility (0.51) is unique to the isolate RS11 from Chintakani mandal (Khammam dist) the most virulent isolate from the study. The last band with Rm value of 0.54 was observed in virulent isolates, RS12, RS17 and RS28. The rice isolate RS 28 has produced maximum number of protein bands followed by RS 16 from Vatsavai mandal of Krishna district indicating their distinct nature of total proteins. This could be due to the genetic change involving the protein production of these isolates. Similarity index (SI) between gross protein patterns of different isolates of R. solani based on SDS-PAGE was found to be high, in the range of 65 to 100%. Maximum SI (100) was observed between the isolates (RS18-RS23) from Nuziveedu and Jangareddygudem mandals and minimum (65.0) SI was observed between the isolates RS7 (from maize) and RS28 (from rice) indicating that the isolates were genetically diverse from each other. Cluster analysis of these isolates based on total mycelial proteins revealed two distinct major and six minor or sub-clusters among the isolates of R. solani. Total banding pattern from the study also revealed that, the highly virulent isolates RS11, RS12 (Khammam), RS16 (Krishna) and RS28 (Rice) were grouped in different subclusters within cluster II along with other isolates from Andhra and Rayalaseema regions. The results revealed that isolates from different localities were more homogenous than isolates from same localities though similarities exist between few isolates of same locality.